2013
DOI: 10.1098/rspb.2012.2228
|View full text |Cite
|
Sign up to set email alerts
|

The genetic rescue of two bottlenecked South Island robin populations using translocations of inbred donors

Abstract: Populations forced through bottlenecks typically lose genetic variation and exhibit inbreeding depression. 'Genetic rescue' techniques that introduce individuals from outbred populations can be highly effective in reversing the deleterious effects of inbreeding, but have limited application for the majority of endangered species, which survive only in a few bottlenecked populations. We tested the effectiveness of using highly inbred populations as donors to rescue two isolated and bottlenecked populations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 69 publications
2
91
2
Order By: Relevance
“…But because recipients and immigrants came from population sources that have been long isolated from one another, and genetic drift is random, introgression between two inbred sources can still result in genetic rescue (Heber et al, 2013). But because recipients and immigrants came from population sources that have been long isolated from one another, and genetic drift is random, introgression between two inbred sources can still result in genetic rescue (Heber et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…But because recipients and immigrants came from population sources that have been long isolated from one another, and genetic drift is random, introgression between two inbred sources can still result in genetic rescue (Heber et al, 2013). But because recipients and immigrants came from population sources that have been long isolated from one another, and genetic drift is random, introgression between two inbred sources can still result in genetic rescue (Heber et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…; Heber et al . ). Most mammals display male‐biased dispersal; that is, males disperse farther and more frequently from the natal home range than females.…”
Section: Introductionmentioning
confidence: 97%
“…Hedrick [235] has shown that gene flow of up to 20% into a recipient population is not likely to swamp locally adapted alleles, particularly those under strong selection. Such genetic rescue/restoration has been successful in several recent cases, such as the Florida panthers, greater prairie chickens in North America, adders in Sweden, South Island robins in New Zealand and mountain pygmy possums in Australia [227,237,238]. However, as with translocations for genetic adaptation above, it is still contentious and has been underutilised as a tool in the conservation of endangered species.…”
Section: Last Ditch Efforts For Critical Speciesmentioning
confidence: 99%
“…Such findings could have important implications for genetic rescue efforts that consider breeding between genetically isolated populations and species, e.g. [226][227][228], but many more studies will be needed before generalisations will emerge. Do climate refugia outside species' current ranges exist and can species reach them?…”
Section: Potential For Naturally Occurring Hybridisation and Introgrementioning
confidence: 99%